EVALUASI PERUMDA AIR MINUM KOTA PADANG DALAM MENGATASI TUNGGAKAN TAGIHAN AIR - Febi Setiawan, Rayhan; Syafril, Rizki (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Customer arrears remain a significant challenge for the Regional Water Company (Perumda) of Padang City, impacting the sustainability of clean water public services. This issue is compounded by the public’s low awareness of timely bill payments and the perception of water as a fundamental right with no financial obligations. Additionally, the inclusion of waste retribution in water bills has led to customer resistance. This study aims to evaluate the effectiveness of Perumda’s policies in managing water bill arrears using a qualitative descriptive approach. Data were collected through in-depth interviews, direct observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings indicate that initiatives such as penalty waivers, installment payment programs, digital payment services, and persuasive field interventions have not substantially reduced arrears. Evaluation against five policy criteria reveals that current policies fail to adequately address all customer segments, particularly those facing economic hardship and low digital literacy. Insufficient outreach and limited human resources further hinder policy success. In conclusion, Perumda’s policies require improved communication strategies, enhanced public education efforts, and optimized digital systems to achieve more inclusive and effective outcomes in promoting customer payment compliance.